Structural defects reference manual for low-rise buildings - Atkinson, Michael F. (London : E and FN Spon, 2000)
The Structural Defects Reference Manual for Low-Rise Buildings has been written to assist professionals and students involved in building construction to identify causes of structural failure. Each chapter carefully addresses design, materials and workmanship factors which contribute to structural defects. The main structural elements - roofs, walls, floors and foundations - are all covered and illustrated by case studies. The book also contains relevant data and guidance to show how all the different building elements should be designed and constructed.
Preface. Chapter 1: Background. Chapter 2: Surveys. Chapter 3: Site Investigation Equipment and Methods. Chapter 4: Structural Reports. Chapter 5: Roofs. Chapter 6: Upper Floors. Chapter 7: Ground Floors. Chapter 8: Main walls. Chapter 9: Foundations. Index.
Includes bibliographical references and index.
Keywords: Buildings -- Defects; Building failures; Building materials -- Defects